VAT Pass-Through: The Case of a Large and Permanent Reduction in the Market for Menstrual Hygiene Products - Alisa Frey; Justus Haucap (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper is about the price effects caused by a VAT (value-added tax) reduction for menstrual hygiene products in Germany. Several aspects make this VAT reduction particularly interesting: The exogeneity of the reduction under otherwise constant economic conditions, the reduction was substantial and permanent, demand for the products is inelastic and in many cases, pass-through rates are more than 100 percent. We find that the VAT reduction is completely passed through to consumers. Despite this complete pass-through, we still detect a significant effect of retailer competition: When more retailers offer a product, the price reduction is larger.
Keywords: H22; H25; H32; K34; 330; VAT reduction; pass-through; hygiene products; retailer competition